Human Papillomavirus (HPV) in oral cavity lesions: comparison with other oral cancer risk factors - Venezuela, Raul Fernando (2013)
Fil: Venezuela, Raúl Fernando. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas; Argentina.